Automatic Software Refactoring to Enhance Quality: A Review - Khaleel, Shahbaa I.; Mahmood , Rasha Ahmed (Universitas Ahmad Dahlan, 2024)
Refactoring aims to enhance the internal structure of the code and improve maintainability without affecting its functionality and external behavior. As a result of the development of technologies, it has become necessary to apply automatic refactoring to address complexities and reduce technical debt. This review presents machine learning and deep learning techniques that lead to identifying opportunities for the need for refactoring and implementing them through analyzing the software code and discovering